Mechanisms underlying the antifungal activity of diethylthiosulfinate against marrow squash wet rot caused by Fusarium solani - Chenxia Liu; Jinglin Zhang; Hui He; Qiankun Wang; Fanjun Kong; Chunfang Wang; Longshen Wang; Xiao Wang; Bingjie Chen; Yuemei Zhang; Junfeng Liu; Yongxing Gu; et al. (International Journal of Food Microbiology, 2026)

Heterometallic 3d-4f MOFs based on a polydentate macrocyclic ligand for photocatalytic CO2 reduction and amine formylation - Yudong Shen; Shuqi Tong; Weile Wang; Bo Li; Shimin Fan; Yunjie Luo; Fanjun Meng; Wei Xu (Chemical Engineering Journal, 2026)

TPGS Modified Phospholipid-free and Cholesterol-free Ethosomes Enhance Chemical Stability and Transdermal Permeation Of Retinol - Fanjun Xu; Meiting Li; Hang Ruan; Teng Guo; Zhi Wang; Nianping Feng; Yongtai Zhang (AAPS PharmSciTech, 2026)

Dual-bactericidal wood-reinforced hydrogel sensor for healthcare monitoring and information transmission - Hengyao Zhou; Hongwei Zhang; Yaobo Wang; Fanjun Yu; Yanjun Xie; Tianpeng Zhang; Zefang Xiao (Chemical Engineering Journal, 2026)

Enzyme-assisted extraction of proteins from radish leaf and their structure-function relationship in stabilizing high internal phase emulsions compared to soy protein and whey protein - Hang Wang; Fanjun Meng; Yinghan Zhao; Yang Liu; Jian Chen; Xiao Liu (Food Hydrocolloids, 2025)

Emulsion coating: One-pot method preparing the sealable microporous surfaces with antibacterial and antithrombotic properties - Jingze Liu; Yueze Hong; Yao Xiong; Yage Hu; Jiaqi Wang; Yuan Wei; Tong Wang; Haichao Yu; Ruipeng Xue; Li Yang; Gaocan Li; Rifang Luo; et al. (Chemical Engineering Journal, 2025)

Recent advances of photocatalysts for nitrogen reduction reaction and mechanism behind them: How and why modifications change properties - Jin Feng; Wenxing Xu; Xiaorui Xu; Xinlu Wang; Yan Wang; Fanjun Zhang; Yuanyuan Feng; Yuchen Ma; Dapeng Zhang (Journal of Environmental Chemical Engineering, 2025)

Allicin derivative (DETS) treatment reduced post-harvest decay in strawberries by inhibiting Botrytis cinerea viability and increasing antioxidant capacity - Chenxia Liu; Fanjun Kong; Yongjin Qiao; Hui He; Chunfang Wang; Qiankun Wang; Xiao Wang; Bingjie Chen; Liqiong Zhang; Wei Xiao; Huali Lin; Biao Jiang; et al. (Food Control, 2025)

Tunicate cellulose nanocrystal reinforced conductive multi-responsive hydrogel with super flexible, fatigue resistant and self-healable capability for antibacterial flexible sensors - Qin Yang; Mingtao He; Zhongrui Yu; Yijie Liu; Yilan Bai; Tianci Liu; Tingting Wang; Lingtao Meng; Fanjun Meng; Qinglin Ma; Yuju Che (Chemical Engineering Journal, 2024)

Formation conditions of soy protein isolate-carrageenan complex particles and their stabilization effect on the relationship between structure and rheology of emulsions - Xiao Liu; Fanjun Meng; Cong Yang; Xiaohui Wu; Miao Wang (Food Bioscience, 2024)

Modification with lignin-based N-P flame retardant to improve the flame retardancy and smoke suppression of wood - Fanjun Yu; Zhichen Ba; Zhizun Gao; Yonggui Wang; Yanjun Xie; Haigang Wang; Zhe Qiu; Zefang Xiao (Chemical Engineering Journal, 2024)

Impact of ε-PL treatment on postharvest quality of ‘Jinxiu’ yellow peach (Prunus persica L.) - Chenxia Liu; Yi Zhang; Hongru Liu; Chunfang Wang; Hui He; Fanjun Kong; Yongjin Qiao (Horticulture, Environment, and Biotechnology, 2024)

Anti-fouling coating with ROS-Triggered On-Demand regulation of inflammation to favor tissue healing on vascular devices - Hui Yan; Lietao Wang; Haoshuang Wu; Yongqi An; Yumei Qin; Zhen Xiang; Huining Wan; Yanfei Tan; Li Yang; Fanjun Zhang; Qing Jiang; Rifang Luo; et al. (Chemical Engineering Journal, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Char and soot records of the Holocene fire history and its implications for climate-vegetation change and human activities within the Guanzhong Basin, southern Loess Plateau, China - Yuzhu Zhang; Qili Xiao; Yan Zhu; Ninglian Wang; Menglei Wu; Yanfeng Li; Jianxi Li; Dou Chen; Xiaoling Huang; Sikai Wang; Pengpeng Cao; Yao Jin; et al. (Science of The Total Environment, 2024)

Rheological and tribological properties of high internal phase emulsions stabilized by pH-induced soy protein isolate-carrageenan complex coacervates - Fanjun Meng; Jiaming Li; Cong Yang; Miao Wang; Xiao Liu (Food Hydrocolloids, 2024)

A photo-triggered coating of prosthetic valve leaflet surface to realize antibacterial and thrombolysis on-demand - Yuan Wei; Xiangling Fan; Jingze Liu; Chong Chen; Ruiqi Dong; Hao Zhang; Li Yang; Rifang Luo; Fanjun Zhang; Yunbing Wang (Chemical Engineering Journal, 2024)

Development of injectable hyaluronic acid-based hydrogels with antioxidant activity for the treatment of corneal neovascularization - Linyu Long; Zhengwei Ge; Fanjun Zhang; Ruiqi Dong; Li Yang; Zhongping Chen; Shibo Tang; Yunbing Wang (Chemical Engineering Journal, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Corrigendum to “Surface modification of titanium implants by pH-Responsive coating designed for Self-Adaptive antibacterial and promoted osseointegration” [Chem. Eng. J. 435 (2022) 134802] - Fanjun Zhang; Qinsheng Hu; Yuan Wei; Weilin Meng; Rong Wang; Jingze Liu; Yong Nie; Rifang Luo; Yunbing Wang; Bin Shen (Chemical Engineering Journal, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Dissecting the phenotypic response of maize to low phosphorus soils by field screening of a large diversity panel - Dongdong Li; Zhe Chen; Meng Wang; Willmar L. Leiser; Thea Mi Weiß; Zheng Zhao; Song Cheng; Shaojiang Chen; Fanjun Chen; Lixing Yuan; Tobias Würschum; Wenxin Liu (Euphytica, 2021)

Glutamine application promotes nitrogen and biomass accumulation in the shoot of seedlings of the maize hybrid ZD958 - Mahmood Ul Hassan; Md Monirul Islam; Ruifeng Wang; Jingyu Guo; Huilan Luo; Fanjun Chen; Xuexian Li (Planta, 2020)

Overexpression of the maize ZmAMT1;1a gene enhances root ammonium uptake efficiency under low ammonium nutrition - Yang Zhao; Zhi Liu; Fengying Duan; Xia An; Xiangguo Liu; Dongyun Hao; Riliang Gu; Zhangkui Wang; Fanjun Chen; Lixing Yuan (Plant Biotechnology Reports, 2018)

ZD958 is a low-nitrogen-efficient maize hybrid at the seedling stage among five maize and two teosinte lines - Jienan Han; Lifeng Wang; Hongyan Zheng; Xiaoying Pan; Huiyong Li; Fanjun Chen; Xuexian Li (Planta, 2015)

Comprehensive phenotypic analysis and quantitative trait locus identification for grain mineral concentration, content, and yield in maize (Zea mays L.) - Riliang Gu; Fanjun Chen; Bingran Liu; Xin Wang; Jianchao Liu; Pengcheng Li; Qingchun Pan; Jordon Pace; Ayaz-Ali Soomro; Thomas Lübberstedt; Guohua Mi; Lixing Yuan (Theoretical and Applied Genetics, 2015)

Mycorrhizal responsiveness of maize (Zea mays L.) genotypes as related to releasing date and available P content in soil - Qun Chu; Xinxin Wang; Yang Yang; Fanjun Chen; Fusuo Zhang; Gu Feng (Mycorrhiza, 2013)